2014
DOI: 10.5653/cerm.2014.41.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between intracytoplasmic sperm injection and intracytoplasmic morphologically selected sperm injection in oligo-astheno-teratozoospermia patients

Abstract: ObjectiveThe aim of this study was to evaluate the efficiency of the intracytoplasmic morphologically selected sperm injection (IMSI) technique compared with conventional ICSI and previous ICSI attempts in oligo-astheno-teratozoospermia (OAT) patients.MethodsThe sperms were selected under high magnification (6,600×) and used to induce fertilization in previous ICSI patients by IMSI. These results were compared with previous conventional ICSI cycles in patients with OAT infertility.ResultsThese results demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…It has been shown that IMSI could improve the IVF results in patients with previous ICSI failures. The pregnancy rate was shown to increase in cases with more than two failed ICSI attempts, also in female infertile with unexplained reasons for failure after ICSI with normal spermatozoa (Kim et al, ; Leandri et al, ; Neyer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that IMSI could improve the IVF results in patients with previous ICSI failures. The pregnancy rate was shown to increase in cases with more than two failed ICSI attempts, also in female infertile with unexplained reasons for failure after ICSI with normal spermatozoa (Kim et al, ; Leandri et al, ; Neyer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…(2002) developed a method called MSOME ( motile sperm organelle morphology examination ), that selects sperm for ICSI using high magnification (> 6000×) in real time, managing to get a better sperm morphologic evaluation, mainly the analysis of the presence of vacuoles in the head (location, size and numbers), aiding in the selection of sperm with better mitochondrial function, intact chromatin, as well as reducing the number of embryos with aneuploidy (Parmegiani et al, 2012). The technique has been successfully used for oligo-asthenoteratozoospermic patients (Kim et al ., 2014) and for couples that had successive implantation failures, reducing clinic abortion rates by 50% (Oliveira et al, 2011). The downside of this technique is that, apart from the high costs, it may take 60-120 minutes from the selection of the sperm to its injection, depending on semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the negative impact of large nuclear vacuoles (LNV) is perceptible after the onset of the EGA, leading to reduced blastocyst formation [28][29][30][31]. Moreover, LNV also affect ongoing pregnancy rates [31][32][33][34], miscarriage rates [31,33,[35][36][37], and malformation in offspring [38,39].…”
Section: Introductionmentioning
confidence: 99%